Beyond procrastination: Enhancing academic self-efficacy to reduce procrastination among students of SMPN X in Malang City - Nurmala, Sukma; Mashuri, Ali; Dara, Yuliezar Perwira; Arifin, Haykal Hafizul (LP2M Universitas Islam Negeri Mataram, 2024)
[Bahasa]: Fenomena prokrastinasi sering terjadi pada pelajar di sekolah, termasuk pada jenjang pendidikan menengah pertama. Pelajar SMP berada di tahap perkembangan remaja awal dengan rentang usia 12-15 tahun. Permasalahan yang sering muncul pada masa remaja, seperti menghindari tugas dan memilih melakukan aktivitas yang lebih menyenangkan, menjadi tantangan yang perlu diperhatikan. Berdasarkan asesmen kebutuhan terhadap pelajar SMP kelas 8 di SMPN X ditemukan bahwa mereka kesulitan mengatur waktu dan cenderung menunda pengerjaan tugas sekolah, terutama yang dianggap sulit. Oleh karena itu, diperlukan suatu intervensi berupa sosialisasi untuk mengenalkan konsep prokrastinasi dan meningkatkan efikasi diri akademik. Intervensi ini dirancang untuk memberikan pemahaman kepada pelajar tentang penyebab dan dampak penundaan tugas sekolah dan strategi untuk mengatasi prokrastinasi. Tujuan dari pengabdian kepada masyarakat ini adalah memberikan edukasi kepada pelajar terkait prokrastinasi dengan menggunakan metode pre-post test. Pretest dan posttest dilakukan dengan menggunakan kuesioner pada awal dan akhir sesi kegiatan. Hasil pengabdian masyarakat menunjukkan bahwa meskipun tidak ada peningkatan yang signifikan pada skor efikasi diri akademik setelah intervensi, namun intervensi ini berhasil meningkatkan rasa tanggungjawab pelajar terhadap hasil belajar mereka. Selain itu, meskipun tidak ditemukan perbedaan skor prokrastinasi yang signifikan sebelum dan sesudah intervensi, pelajar yang melaporkan penurunan prokrastinasi cenderung mengalami peningkatan efikasi diri akademik sebagai dampak dari intervensi tersebut. Kata Kunci: efikasi diri akademik, pelajar SMP, prokrastinasi, rasa tanggungjawab, remaja awal [English]: The phenomenon of procrastination is often observed among students at school, including those at the junior high school level. Junior high school students are in the early adolescent stage, ranging from 12 to 15 years old. Common issues during adolescence, such as avoiding tasks and engaging in more enjoyable activities, present challenges that require attention. A needs assessment conducted among 8th-grade students at SMPN X revealed that they face difficulties in time management and tend to postpone completing school assignments, particularly those perceived as challenging. Therefore, an intervention through a socialization program is necessary to introduce the concept of procrastination and enhance academic self-efficacy. This intervention was designed to provide students with an understanding of the causes and consequences of procrastination and strategies to overcome it. This community service aims to educate students about procrastination using a pre-test and post-test method. Pre-tests and post-tests were conducted using questionnaires at the beginning and end of the sessions. The results of the community service program indicated that, although there was no significant increase in academic self-efficacy scores after the intervention, the program successfully improved students' sense of responsibility for their learning outcomes. Furthermore, while no significant differences were found in procrastination scores before and after the intervention, students who reported a decrease in procrastination tended to experience an increase in academic self-efficacy as an effect of the intervention. Keywords: academic self-efficacy, early teens, junior high school students, procrastination, sense of responsibility